Strategi dan Solusi Pengembangan Usaha Perkebunan Jeruk untuk Meningkatkan Daya Saing: Studi Kasus Perkebunan Jeruk Salit di Kabanjahe - Marito Ritonga; Fadli Agus Triansyah; Andi Cici Thania; Nela Permata Sari Lubis; Ananda Christopher Lumbantoruan; Artika Rahma Dani (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the management and development strategies of a citrus farming enterprise to enhance competitiveness at the Salit Citrus Plantation in Kabanjahe. A qualitative approach with a case study design was employed, utilizing semi-structured interviews, field observations, and documentation. Informants were selected purposively and consisted of the plantation owner, farm workers, and visitors participating in the citrus-picking tourism activity. Data were analyzed thematically through coding and categorization to identify cultivation strategies, marketing practices, and challenges in business development. The findings show that the plantation is managed using traditional yet consistent practices, including scheduled fertilization, routine pest control, and annual manual harvesting. Marketing strategies are carried out through direct selling and agritourism activities, which provide added value and strengthen relationships with consumers. The plantation also faces several challenges, such as fruit fly infestations, limited utilization of citrus waste, price fluctuations, and insufficient government support. These findings indicate that the combination of consistent cultivation practices, direct marketing, and the development of agritourism plays an essential role in enhancing the competitiveness and sustainability of small-scale citrus farming enterprises.